First, add color(red)(10) to each side of the equation to put the equation in standard form:
x^2 - 3x + color(red)(10) = -10 + color(red)(10)
x^2 - 3x + 10 = 0
We can use the quadratic equation to solve this problem:
The quadratic formula states:
For color(red)(a)x^2 + color(blue)(b)x + color(green)(c) = 0, the values of x which are the solutions to the equation are given by:
x = (-color(blue)(b) +- sqrt(color(blue)(b)^2 - (4color(red)(a)color(green)(c))))/(2 * color(red)(a))
Substituting:
color(red)(1) for color(red)(a)
color(blue)(-3) for color(blue)(b)
color(green)(10) for color(green)(c) gives:
x = (-color(blue)(-3) +- sqrt(color(blue)(-3)^2 - (4 * color(red)(1) * color(green)(10))))/(2 * color(red)(1))
x = (3 +- sqrt(9 - 40))/2
x = (3 +- sqrt(-31))/2